Model pembelajaran bahasa Arab dalam Kurikulum Berbasis Cinta di madrasah - Yesika Alfianingsih; Ahmad Riyadissolihin; Khaerul Muttakin; Muhajir Muhajir; Dewi Atma Junira; Helmi Najamudin (Universitas Pendidikan Indonesia, 2026)
The implementation of the Kurikulum Berbasis Cinta is still dominant at the conceptual and policy levels, while operational learning models, especially for Arabic, have not been systematically formulated. This study aims to describe and formulate an Arabic language learning model that integrates the values of compassion, empathy, and humanism throughout the learning process. This study uses a descriptive, qualitative approach grounded in a literature review, drawing on policy documents, books, scientific articles, and relevant prior research. The results show that the Arabic language learning model in the Kurikulum Berbasis Cinta has four main characteristics, namely 1) Learning objectives that combine mastery of four language skills with the internalization of the values of love and empathy; 2) Learning materials that integrate linguistic texts with Qur'anic values, humanity, and the lives of students; 3) A learning approach that applies compassionate pedagogy and collaborative learning to create a safe and inclusive learning environment; 4) Learning evaluation that assesses students' learning processes, attitudes, and development. These findings confirm that the model can serve as a pedagogical strategy and a humanistic, operational, and relevant framework for learning Arabic, suitable for implementation in madrasas.